2016
DOI: 10.18261/issn.1891-943x-2016-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of tablets in primary and secondary school - a case study

Abstract: Norwegian schools are increasingly implementing tablets in school and there seems to be a need for more research within this area to examine how this implementation affects pupils' learning processes. This article focuses on the use of tablets in pupils' learning and the extent to which pupils become more involved in the planning, implementation and assessment of their learning. We used a qualitative research approach and case study to investigate six classes at three different schools: four classes in one pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
(39 reference statements)
2
17
0
1
Order By: Relevance
“…The perspective of learning and remembering better while taking notes was also found in a Norwegian case study, where the participants were in the same age group as the present study. Even though the findings on a general level showed that the use of tablets made writing easier, some of the students related that they learned better if they wrote by hand (Kongsgården & Krumsvik, 2016). Similar results were reported by Longcamp, Zerbato-Poudou, and Velay (2005), and Longcamp et al (2008).…”
Section: Previous Researchsupporting
confidence: 78%
“…The perspective of learning and remembering better while taking notes was also found in a Norwegian case study, where the participants were in the same age group as the present study. Even though the findings on a general level showed that the use of tablets made writing easier, some of the students related that they learned better if they wrote by hand (Kongsgården & Krumsvik, 2016). Similar results were reported by Longcamp, Zerbato-Poudou, and Velay (2005), and Longcamp et al (2008).…”
Section: Previous Researchsupporting
confidence: 78%
“…The use of information technology in education has the potential to change the boundaries of classrooms in traditional schools and classrooms [1,2]. As an instructional technology that is expanding rapidly, the use of tablets in classroom instruction can enrich students' interactive and collaborative activities, enhance classroom engagement, and assist in a variety of instructional contents and applications for learning and teaching [3][4][5][6][7]. Additionally, educational tablet use can lead to advances in the interactivity of the educational process between teachers and students or among students.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics of tablets in relation to classroom use are helping to transform the instructional paradigm from a teacher-centered approach to a student-centered approach, which can encourage both teachers and students to engage actively in instruction [20]. To accomplish this technology-based transformation in the classroom, the teacher's role and behavior in using such technology to support students' learning is important [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Undersøkelsen viser at laererens digital-didaktikk og undervisningsdesign spiller en sentral rolle i elevenes laering og for at elevene skal lykkes til eksamen. Gjennom å fokusere på prosesser framfor produkt (Krumsvik, 2012;Andrade, 2013;Black, 2016;Kongsgården & Krumsvik, 2016) kan det synes som at laereren vektlegger tilbakemeldinger og interaktive laeringsprosesser som involverer elever og laerere i et laeringsfellesskap, eller det Fullan og Langworthy (2014) betegner som «partnerskap i laering». Man kan også registrere at laeringsmål og kriterier for måloppnåelse har et gjennomgående fokus i alle emnene i faget og kan bidra til en mer markant dybdelaering (Pellegrino & Hilton, 2012) for elevene.…”
Section: Laererrollenunclassified